Manajemen Waktu Ibadah Terhadap Budaya Nongkrong Mahasiswa Gen Z Dalam Pandangan Islam - Eka Ananda Syafira, Salsabilla Rahmanda Bya Siagian, Raihani Salsa Billa, Ravisa, Suci Nabiella, Hap (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2026)
This study aims to analyze the relationship between the hangout culture of Generation Z students and prayer time management from an Islamic perspective. The phenomenon of hanging out has now become part of the student lifestyle as a means of socializing, discussing, and filling free time. However, this activity has the potential to affect students' discipline in performing their prayers if not managed properly. This study used a descriptive method with qualitative and quantitative approaches through a survey. Data were obtained through an online questionnaire distributed using Google Forms to 48 Muslim student respondents from several universities in Medan City. The results showed that hanging out is quite frequently engaged in by students as part of their social lives. Despite this, most students still strive to maintain their religious obligations by managing their time so that social activities do not interfere with their religious obligations. However, some respondents also admitted to having postponed prayers due to excessive hanging out. From an Islamic perspective, hanging out is essentially permissible as long as it does not neglect religious obligations and remains within reasonable limits. Therefore, students are expected to be able to manage their time wisely to balance social activities and spiritual responsibilities in their daily lives.